2018
DOI: 10.1002/ajh.25133
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐DRB3/4/5 mismatches are associated with increased risk of acute GVHD in 10/10 matched unrelated donor hematopoietic cell transplantation

Abstract: Matching for HLA-A, -B, -C, and -DRB1 loci (8/8 match) is currently the gold standard for unrelated donor hematopoietic cell transplantation (HCT). In Europe, patients are also matched at the HLA-DQB1 loci (10/10 match). However, there is increasing evidence that matching at HLA-DRB3/4/5 loci may help to lower transplant-related morbidity and mortality. We therefore investigated the impact of HLA-DRB3/4/5 mismatches on outcomes in 1975 patients who received a first 10/10 matched unrelated donor (MUD) HCT in Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 16 publications
2
14
0
1
Order By: Relevance
“…An impact of HLA-DRB3/4/5 mismatch on OS has not yet been described in other studies ( 11 , 12 ). This might be attributed to the relatively high percentage of older patients included in this study (i.e., 30% >60 years and 54 years median age), given that HLA-associated risk increases with age particularly with regard to transplant-related morbidity ( 26 ).…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…An impact of HLA-DRB3/4/5 mismatch on OS has not yet been described in other studies ( 11 , 12 ). This might be attributed to the relatively high percentage of older patients included in this study (i.e., 30% >60 years and 54 years median age), given that HLA-associated risk increases with age particularly with regard to transplant-related morbidity ( 26 ).…”
Section: Discussionmentioning
confidence: 79%
“…Although statistical significance was not reached in the aGvHD models including only HLA-DRB3/4/5 ARD-mismatched cases, the analysis in a model encompassing all types of HLA-DRB3/4/5 mismatches revealed a statistically significant higher risk of aGvHD II–IV in the complete cohort (HR 1.21, 95% CI 1.02–1.43, p = 0.027). The inability to clearly identify this effect in the HLA-DRB3/4/5 ARD-mismatched cases alone is more likely due to a lack of statistical power rather than lack of association, considering that previous studies have already shown a significantly higher risk of aGvHD in patients receiving HLA-DRB3/4/5- mismatched grafts ( 10 , 11 ). Having said that, an additive effect of HLA-DRB4 E3 mismatches cannot be excluded ( 11 ), despite the common perception that mismatches not affecting the ARD have a low impact on alloreactivity ( 27 ).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…A retrospective multicentre French study of 1,975 patients with haematological malignancies who received 10/10 matched unrelated donor transplant showed significant increased risk of grade II‐IV aGvHD in pairs with HLA‐DRB3, DRB4, DRB5 mismatches when compared with those with no mismatch at these loci. There was no difference in cGvHD, NRM, relapse and OS between these two groups (Ducreux et al., 2018).…”
Section: Histocompatibility Matching: Volunteer Unrelated Donor Selecmentioning
confidence: 99%